Fostering accountability using evidence to guide and improve child welfare policy - Testa, Mark.; Poertner, John. (New York ; Oxford : Oxford University Press, 2010)
This work presents a model of child welfare decision making that holds public officials answerable for the integrity and validity of the actions they take on behalf of the children and families in their care.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child welfare -- Government policy -- United States; Foster home care -- United States; Child welfare -- United States; Family services -- United States